Peritraumatic Pain in Child Sexual Abuse: Children’s Descriptions of Pain as Conveyed in Their Testimonies Following Child Sexual Abuse - Tsur, Noga (Journal of interpersonal violence, 2022)
The literature on child sexual abuse (CSA) has contributed significantly to the understanding of its characteristics, epidemiology, and consequences. Considerably less attention has been dedicated, however, to the subjective experiences of the abused children, and more specifically to their experiences of pain. The current study explored the way children perceive and describe pain during and shortly following incidents of sexual abuse. The sample was comprised of 35 transcripts of forensic interviews following alleged CSA. Thematic analysis of the children?s narratives identified three themes: (a) pain during the abusive incidents, described using words indicating its intensity and quality; (b) pain shortly after the abusive incidents, including weeks later, and (c) pain as embedded within the complex dynamic with perpetrator. The children struggled to localize the pain, mainly using words such as ?inside? and ?deep.? Moreover, they testified that in the course of the abusive incidents, they were often silenced when trying to communicate their pain to the perpetrators. The children?s narratives provided us with a unique opportunity to learn about the pain not only during the abusive incidents but also following it. Additionally, children described suffering from pain in areas that were not directly injured during the CSA incidents, mainly referring to the head, abdomen and legs. The discussion addresses the potential intervening factors in peritraumatic CSA pain, as well as its potential links with chronic post-traumatic physical and mental morbidity. This study illuminates the necessity to address the complicated links between short- and long-term physical, emotional, cognitive, and interpersonal manifestations of CSA.